PENGARUH KEPEMIMPINAN, KOMUNIKASI DAN SOSIAL EKONOMI TERHADAP PARTISIPASI MASYARAKAT DI NAGARI BATANG PALUPUAH KABUPATEN AGAM - Efalia Arna; Yulihasri (Jurnal Ekonomi, Bisnis dan Manajemen, 2022)
This study aims to examine the influence of leadership, communication, and socio-economics on community participation in cooperation activities in Nagari Batang Palupuah, Agam Regency. The sample in this study used non-probability sampling with a purposive sampling technique using a questionnaire distributed to 60 respondents. This study uses data analysis techniques with a Structural Equation Model (SEM) approach. The results of this study found that leadership has a positive effect on community participation in cooperation activities in Nagari Batang Palupuah, Agam Regency with a lower significance value of 0.000 so that the proposed hypothesis can be accepted. Then communication has a positive and significant influence on community participation in cooperation activities in Nagari Batang Palupuah, Agam Regency with a set significance value of 0.000 so that the hypothesis can be accepted. Furthermore, Socio-Economic has a positive effect on community participation in cooperation activities in Nagari Batang Palupuah, Agam Regency with a smaller significance value set at 0.000 so that the hypothesis can be accepted. This research implies that good leadership and communication, as well as socioeconomic, can increase community participation in gotong royong activities.